Pengaruh Syariah Strategi Marketing terhadap Volume Penjualan Baju di Purnama Store Medan dengan Customer Satisfaction sebagai Variabel Intervening - Annisa Ritonga (Masyarakat Ekonomi Syariah Bogor, 2023)
The decline in sales volume at the Purnama Store was the reason for the various reasons for the decline. Among them is the influence of the lack of consumer satisfaction and the implementation of sharia marketing strategies that are not implemented as well as other reasons such as the influence of material quality, promotional prices and others. Therefore this study aims to determine the causes of the decrease in sales volume at the Purnama Store from the influence of customer satisfaction and sharia marketing strategies. Using the PLS (Partial Laest Square) data analysis method will issue results on how the influence of consumer satisfaction, sharia marketing strategy and sales volume. The highest percentage gave reasons for the decrease in sales volume of clothes at the Purnama Store. This research is quantitative, using primary data by collecting various answers to questions given to Purnama Store customers. The related data were analyzed using the Microsoft Excel 2019 program. Meanwhile, the data analysis technique used PLS (Partial Laest Square) analysis, the Valid and Reali test method, Outer Model and Inner Mode, and Derect Effect and Inner Effect hypothesis testing. The results showed that there was no influence of sharia marketing strategy on the volume of clothing sales, because based on the T-Statistics value, the most significant percentage of influence on sales volume came from customer satisfaction with a P Value of 35,097. Keywords : Syariah Strategi Marketing, Customer Satisfaction, Volume Penjualan.